Improving Students Listening Comprehension with Mobile App “English Listening Test” - Alit Eka Handayani; Lidiyatul Izzah (English Language in Focus (ELIF), 2020)
The use of Android smartphones will improve the skills of English Language Learners to the segments of the level they want to achieve. Language students are able to select the various android apps as necessary, such as speaking, listening, reading, writing, components of languages, vocabulary mastery, and even sentence structure in English. This can be used as an English aid by all levels of learning or can be used as a media resource. The purpose of the study was to find out the use of the Mobile-based English Listening Test App enhances students' listening comprehension. The methodology towards this research was quantitative. This research used a pre-experimental sampling frame using pre-test and post-test. In collecting the data, the researchers used the listening test as an instrument. The subjects of the research were SMK Gelora Bekasi's 10th grade students. The result reveals that the total student post-test score in the experimental class was higher (15,871) than in the control class (2,028). Based on the t-test, above 15,871 average result was obtained at the level of freedom (df) of 36 (36-1 = 35), while 2,028 of of average result was obtained at the level of significance of 5 percent. Since t0 is higher than the tt score obtained from the results of the calculation, a positive hypothesis (H1) can be acknowledged. The hypothesis finding implies that the use of the Mobile English Listening Test App enhances students' comprehensive listening skills.